Da'wah communication strategy for strengthening wasathiyah Islam in Surabaya: A case study of NU, Muhammadiyah, and Al-Irsyad - Pardianto, Pardianto; Syam, Nur; Nurdin, Ali (Jurnal Ilmu Dakwah, 2025)
Purpose - This study aims to describe the communication strategies used by Islamic social organizations, NU, Muhammadiyah, and Al-Irsyad, in strengthening Islam wasathiyah in the city of Surabaya. Method - Employing a qualitative phenomenological approach and using in-depth interviews with Islamic organizational figures. Result - The research identifies five key strategies of da'wah communication: an integrated cultural strategy, a curriculum-based educational strategy, a social synergy strategy, a media-based strategy, and a collaborative strategy. Implication – This study could encourage the activists of da’wah within Islamic organizations in Indonesia to a synergize their approach in disseminating wasathiyah Islam teachings as well as inclusive religious understanding. Originality/Value - The novelty of this study lies in the up-to-date description of the dynamics of Islamic organizations’ da’wah communication strategies in Surabaya, particularly to strengthen Islam wasathiyah. Moreover, this study led to the discovery of “a synergistic moderate da'wah communication strategy”, which proposes that harmony between Islamic social organizations’ approach to disseminating moderate da'wah messages will create an inclusive religious understanding, thereby strengthening wasathiyah Islam in society. *** Tujuan  - Studi ini bertujuan untuk menguraikan strategi komunikasi dakwah organisasi sosial keislaman dalam memperkuat  Islam wasathiyah di Kota Surabaya. Metode - Peneliti menggunakan metode penelitian kualitatif, pendekatan fenomenologi, dan wawancara mendalam dilakukan kepada para tokoh dari ketiga organisasi keagamaan. Hasil - Hasil penelitian menunjukkan bahwa strategi komunikasi dakwah organisasi sosial keislaman  dalam memperkuat Islam wasathiyah di kota Surabaya mencakup beberapa strategi yaitu; strategi kultural terintegrasi, strategi pendidikan berbasis kurikulum, strategi sinergi sosial, strategi  melalui media, dan strategi kolaborasi. Implikasi– Penelitian ini dapat mendorong para pegiat dakwah antar organisasi sosial keagamaan di Indonesia untuk melakukan pendekatan komunikasi dakwah yang sinergis dalam upaya menyebarluaskan ajaran Islam wasathiyah sekaligus pemahaman keagamaan yang inklusif. Orisinalitis/Nilai – Kebaruan studi ini terletak pada deskripsi terkini tentang dinamika strategi komunikasi dakwah organisasi sosial keagamaan di Surabaya, khususnya dalam memperkuat Islam wasathiyah. Lebih lanjut, studi ini menghasilkan temuan "strategi komunikasi dakwah moderat bersinergi", dengan proposisi bahwa keselarasan antara pendekatan Ormas Islam dalam menyebarkan pesan dakwah moderat akan menciptakan pemahaman keagamaan yang inklusif, sehingga memperkuat Islam wasathiyah di masyarakat.